Modéliser et comprendre les campagnes de la Somme romaine à l’aide des systèmes d’information géographique - Nicolas Revert (Humanités Numériques)
One of the functions of archaeological GIS is modelling, with the aim to propose a spatial hypothesis rather than raw data. This paper consists in presenting the design, results and limits of spatial modelling through GIS, which are applied to the rural settlement of the Somme in the Roman era. Its purpose is to ascertain locational parameters, i.e. the human decisions which condition the presence of a site in a specific area. In the Somme, variables that have a statistical impact on the spatial distribution of farms and villae tend to pertain more often to the socio-economic field rather than the physical environment. While the gap in the archaeological data and reconstituted variables is real, it is undeniable that GIS models allow a finer and more reliable understanding of ancient landscapes and their interaction with the inhabitants.